Psychopathy and Victim Selection: Does Nonverbal Decoding or Empathy Impact Vulnerability Ratings? - Denardo Roney, Julia L. (Journal of interpersonal violence, 2021)
This research examined the role of psychopathic traits in perceptions of victimization and vulnerability. Community-member participants viewed video clips of victims, nonvictims, and victims who studied self-defense, then rated them on vulnerability and perceived history of victimization. Participants were most proficient at identifying nonvictims as nonvictims. Victims who studied self-defense were harder to correctly identify than both victims and nonvictims and were rated by participants as less vulnerable and less likely to be victims than other victims and nonvictims. Moreover, individuals high in psychopathic traits, specifically Factor 2, were more likely than individuals low in psychopathic traits to correctly identify victims who practiced self-defense as victims, as well as nonvictims as victims. Unexpectedly, there was an observed negative relationship between facial affect decoding and identifying self-defense victims. The ability to correctly interpret facial expressions was found to partially mediate the relationship between psychopathy scores and the identification of self-defense victims. The results of this study provide insight into the ability of individuals with psychopathic traits to identify nonverbal cues associated with vulnerability. The results provide evidence that taking self-defense classes may be a meaningful intervention for victims, particularly.